Tempest [videorecording (DVD)] - Mazursky, Paul; Mazursky, Paul; Mazursky, Paul; Cassavetes, John, 1929-1989; Rowlands, Gena; Sarandon, Susan, 1946-; Gassman, Vittorio (Sony Pictures Home Entertainment, 2007)
Comedy loosely based on Shakespeare's play "The Tempest" has a New York City architect who tries to solve his midlife crisis by moving to a Greek island with his teenage daughter.